Analysis of Wave Tusing Patterns In Hadrah Art In Lubuk Dagang Village, Sambas District - Nurizki, Elvin; Olendo, Yudhistira Oscar; Silaban, Chiristianly Yery (International Journal of Learning and Instruction (IJLI), 2024)
This study discussed the arts in Sambas, West Kalimantan, namely hadrah singing poetry praising the greatness of God and the 'Wave' drum pattern and techniques for playing the "Wave" drum pattern in the Hadrah art in Lubuk Dagang Village, Sambas Regency. The problem in the research is how the 'Wave' Drum Pattern and the Technique for Playing the 'Wave' Beat Pattern in Hadrah Art in Lubuk Dagang Village, Sambas Regency. The method in this research is descriptive analysis in the form of qualitative research. The approach used in this research is musicological. The data sources in this research are the results of interviews with various artists and actors in the "Hadrah" "Lubuk Dagang" arts, namely Afdan, Marzuki, and Iman. The data collection tools for this research are interview guides, observation guides, notebooks, and cameras. The technique for testing the validity of the data in this research is triangulation and extended observations. The result of this research is the "Wave" drum pattern using a 4/4-time signature. The instrument used in this game is tahar/tar. The drum pattern is parent, one child and two children. The "main" tahar functions to maintain the tempo and build rhythmic patterns which are formed into a variety of drumming patterns, the "child 1" tahar functions to interrupt the "main" tahar while the "child 2" tahar has a drum pattern that alternates between the "main" tahar and the "parent" tahar. Child 1". The number of players consists of 3 to 5 people depending on the agreement that has been agreed on how many musicians and poets are desired in the performance. Conclusion Tahar is a traditional percussion musical instrument. The sound source of this instrument comes from a flat, circular membrane or skin with a combination of rattles on the sides of the musical instrument.  Keywords: Analysis, Wave Tusing Patterns, Hadrah